Formal evaluation in philosophy: considerations adresseds to the high school - Marcelo Prates; Antonio Carlos Persegueiro (Universidade Federal de Santa Catarina, 2017)
The text approaches the formal evaluation and it discusses the resumption of meaning along the development and operationalization of this activity. Focuses on the Discipline of Philosophy, offered in High School (General Education and Vocational College) and indicates the condition of greater proximity between students and the Program Contents.  Therefore, it seeks exalt the dialogue and the mediation, indelible capabilities to the teacher, directing them for the evaluations activities. In so doing, considered the obligation of those referred in this and others phases of school education, in way the teacher may cultivate and,  constantly, upgrade the meaning of the formal evaluations, especially in the steps of preparation and application? In order to offer a propositive response, resorts to the specific way, the National Curriculum Guidelines, in part designed to Philosophy. However, not to incur general enunciations, or that flee the question, will be conjugates the indications stemming to the Basic Education Curriculum Guidelines/SEED-PR. Through the present convergence, contributions received will be directed to settle the claims arising in the evaluation field, inevitable to the undergraduates and graduates of the Degrees in Philosophy.